Komunikasi Pemasaran dalam Pemberdayaan UMKM di Desa Pedagangan Kecamatan Tiris, Kabupaten Probolinggo - Amri, Novan Barliandry; A’yun, Ariza Qurrata (Journal of Management, Education and Communication, 2025)
Marketing communication is an important element in connecting MSME products with a wider market, especially in the context of villages that still face various limitations in terms of access to information and technology. This study aims to analyze the role of marketing communication in empowering Micro, Small, and Medium Enterprises (MSMEs) in Pedagangan Village, Tiris Subdistrict, Probolinggo Regency. The research method used is a qualitative descriptive approach with data collection techniques through observation, in-depth interviews, and documentation of MSME actors and related parties such as village officials and business assistants. The results of the study show that the marketing communication strategies implemented by MSME actors in Pedagangan Village are still traditional, such as word-of-mouth marketing and direct sales in local markets. However, there are empowerment efforts from various parties, including the village government and supporting institutions, to improve the ability of business actors to utilize digital platforms such as social media  as a means of promoting and distributing products.